After the Damages: an International Summer School for Risk Prevention, Management and Design (diségno, 2020)
The first edition of the Summer School “After the Damages” ended in July 2020. The initiative aimed at increasing both the resilience capacity (natural and anthropic) and the mitigating and management aspects in case of catastrophic or calamitous events. Starting from the assumption that the damages caused by such situations and their consequences, which generally have a major impact on society, cannot be quickly solved, the training course worked on the limits of tolerance to their effects, aiming at their possible increase in order to reduce the level of potential disaster (read more).